Ultrasound and Clinicopathological Characteristics of Triple Receptor-Negative Breast Cancers - Choi, Yoon Jung (Korean Breast Cancer Society, 2011)
PURPOSE: Triple receptor-negative (TRN) breast cancer is associated with high risk of recurrence and poor prognosis. The present study assessed the clinicopathologic characteristics and ultrasound (US) features of TRN breast cancers. METHODS: Pathological and biological data were reviewed for 558 breast cancer patients treated at Kangbuk Samsung Hospital, between January 2003 and December 2009. The patients were separated into TRN breast cancer and non-TRN breast cancer groups, based on the results of immunohistochemical prognostic panels. Clinical and pathologic features were compared for the two groups. US features, including shape, orientation, margins, boundaries, echo patterns, posterior acoustic features, surrounding tissues, and microcalcifications, were determined for 41 TRN patients and 189 non-TRN controls (ER+/PR+/HER2-). RESULTS: Of 558 cases, 58 (10.4%) had the TRN phenotype. Four hundred and thirty-four cases (77.8%) were invasive ductal carcinomas. TRN cancer was significantly associated with specific characteristics of tumor size, nuclear grade, histologic grade, venous invasion, and lymphatic invasion. With respect to US features, TRN cancers were more likely to have an oval shape, a circumscribed margin, and marked hypoechogenicity. CONCLUSION: Tumor characteristics were different between TRN and non-TRN breast cancers, although US cannot differentiate the subtype of breast cancers TRN cancer tend to show somewhat different US morphology.